The failure of prisons in fostering and re-socializing prisoners - Henky Fernando (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2023)
Fostering and re-socializing prisoners lead to misconduct that results in prison failure. The studies have only concentrated on forms and factors when discussing this phenomenon, neglecting a comprehensive exploration of the implications of prison failure. This study focuses on the question, "What are the implications of prison failure on the conditions and behavior of prisoners after undergoing fostering in prison?" This study uses a descriptive-qualitative netnography method to investigate the forms, factors, and implications of prison failure on the conditions and behavior of prisoners forced to undergo fostering in prison described through online media coverage. This study's findings reveal that prisons fail, as evidenced by criminal events that counter the guidance orientation. Prison failure occurs due to the weak commitment of institutions and prison officials in actualizing the objectives of fostering, which systemically leads to recidivism with repeated criminal cases and actions. This study also recommends the importance of interviewing officers and prisoners undergoing the fostering process in prison to obtain a more comprehensive and empirical understanding.